Zinc chelates as new activators for sulphur vulcanization of acrylonitrile-butadiene elastomer (eXPRESS Polymer Letters)
The goal of this work was to apply several zinc chelates as activators for sulphur vulcanization of acrylonitrilebutadiene elastomer (NBR), in order to find alternatives for the conventionally used zinc oxide. In this article, we discuss the effects of different zinc complexes on the cure characteristics, crosslinks distribution in the elastomer network and mechanical properties of acrylonitrile-butadiene rubber. Zinc chelates seem to be good substitutes for zinc oxide as activators for sulphur vulcanization of NBR rubber, without detrimental effects on the crosslinking process and physical properties of the obtained vulcanizates. Moreover, application of zinc complexes allows to reduce the amount of zinc ions in rubber compounds by 40% compared to conventionally crosslinked vulcanizates with zinc oxide. It is a very important ecological goal since zinc oxide is classified as toxic to aquatic species and its amount in rubber products must be reduced below 2.5% at least. From a technological point of view it is a very important challenge.